High-fidelity color characterization in virtual reality across head mounted displays, game engines, and materials - Díaz-Barrancas, Francisco; Rodríguez, Raquel Gil; Bayer, Florian S.; Aizenman, Avi; Gegenfurtner, Karl R.; Justus Liebig University Giessen (My University, 2024)
We present a comprehensive colorimetric analysis of three head mounted displays (HMDs) - HTC Vive Pro Eye, Pimax 8K X DMAS, and Varjo Aero - focusing on their color calibration and uniformity across different game engines (Unity and Unreal) and for different materials/shaders. We developed a robust methodology combining hardware and software tools, including spectroradiometry and imaging colorimetry, to characterize and calibrate these HMDs for accurate color reproduction. The study showcases substantial advancements in colorimetric accuracy, with a reduction in the average deltaE00 of 90% or more across all tested HMDs and conditions. This level of color reproduction quality is below human discrimination thresholds, ensuring that any color inaccuracies remain imperceptible to the human eye. We also identified key areas for improvement, particularly in display uniformity, which could impact peripheral color reproduction. By making our tools and code publicly available, this study aims to facilitate future research and development in virtual reality (VR) technology, emphasizing the importance of color fidelity in virtual environments. The new insight enabled by our work is the extension and application of a traditional calibration method to currently available HMDs.
Keywords: ddc:150